Bean grain hysteresis with induced mechanical damage - Campos,Renata C. (2016)
ABSTRACT This study aimed to evaluate the effect of mechanical damage on the hysteresis of beans with induced mechanical damage under different conditions of temperature and relative humidity. Beans (Phaseolus vulgaris L.) harvested manually with 35% water content (w.b.) were used. Part of this product was subjected to induced mechanical damage by Stein Breakage Tester and controlled drying (damaged and control sample), for sorption processes. The sorption isotherms of water were analyzed for different temperature conditions: 20, 30, 40 and 50 oC; and relative humidity: 0.3; 0.4; 0.5; 0.7 and 0.9 (decimal). Equilibrium moisture content data were correlated with six mathematical models, and the Modified Oswin model was the one that best fitted to the experimental data. According to the above mentioned isotherms, it was possible to observe the phenomenon of hysteresis of damaged and control samples, and this phenomenon was more pronounced in control ones.